THE APPLICATION OF JIGSAW TECHNIQUE IN TEACHING SPEAKING IN INDONESIAN CONTEXT - Ayuna Netta (Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2022)
This article is a review of the application of jigsaw technique in teaching speaking in Indonesian context. It aims at investigating the implications and the challenges faced in using jigsaw in teaching speaking. This is a library research which compiles the findings of the researches which focus on the application of Jigsaw in teaching speaking in Indonesia. Due to the limitation of this study, it only takes twelve articles or journals to be reviewed. The finding shows that most of the teachers or lecturers and students who conduct the teaching-learning process by using jigsaw technique experience a lot of advantages rather than disadvantages. However, the disadvantages could also find in the application of jigsaw technique in the class. The advantages of using jigsaw in teaching speaking are Jigsaw could motivate the students, improve their ability in speaking, encourage students to be more active, introduced new vocabulary, improve their social language, makes the teaching and learning process becomes more appealing and dynamic, and increases the students’ confidence in speaking in front of the class. While, the disadvantages of using Jigsaw technique in teaching speaking are it could not be used in challenging subject, young learners or children are unable to follow procedures and instructions appropriately, bore the class and needs extra time, the teachers could not monitor their students' activities, and the students feel difficult to express themselves.